Closer to the problem: can a virtual prison arts event foster psychological proximity to the issue of incarceration?. Issue 1 (2nd January 2022) - Littman, Danielle Maude; Sliva, Shannon M.; Lin, Jeffrey
ABSTRACT: Prisons are physically separated from society. As a result, the public has little contact with incarcerated people, and few avenues for understanding their lived experiences. Our evaluation draws upon construal level theory – the idea that the more concrete something becomes, the more psychological proximity we perceive – to consider whether attending a virtual prison arts event may foster psychological proximity to incarcerated individuals and issues of incarceration among the general public. Further, we consider whether increased psychological proximity is associated with shifts in attitudes towards, and intentions to act regarding, issues of incarceration. We found that attendees (N = 142) who had been inside prisons previously had higher levels of psychological proximity at pretest. All attendees demonstrated significant increases in psychological proximity between pretest and posttest; attendees who had not visited prisons previously experienced greater changes. Increases in psychological proximity were predictive of changes in attitudes and intended behaviors. Our findings foreground the need for research which explores what kinds of events, and for whom, these effects are most impactful. Lastly, we suggest that policymakers and practitioners consider virtual gatherings and arts events as a cost-effective, yet meaningful, way to bridge the gap between incarcerated people and communities.